Employer brand: experience dimensions, components, and appeals in a telecommunications company. (2024)
This article examines the concept of employer branding through its dimensions of experience, components, and appeals. The research is based on a case study of a mobile telecommunications company (Tigo) with a focus on the experience centers in Barranquilla, Colombia. The study, with a descriptive scope, applied a quantitative survey technique to 107 employees in roles such as administrators, coordinators, and commercial advisors. The survey instrument was constructed through literature review, and measurement questions were identified through expert validation. The results indicate that employees perceive the dimensions of employer branding experience, components, and appeals positively. Although components of employer branding showed a lower average compared to other concepts, they remained positive for the company. These findings are relevant for understanding employer branding in customer interaction areas such as experience centers.